Subjective improvement of hearing through cochlear implantation - Volleth, Nadine; Hast, A.; Lehmann, E. K.; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: During the past few decades various questionnaires have been developed to evaluate quality of life using audiological measures. The Hearing Implant Sound Quality Index (HISQUI) was developed especially for patients with a cochlear implant (CI). The aim of this study was to evaluate subjective hearing improvement after CI surgery and to correlate the results with objective measuring methods such as pure-tone and speech audiometry. MATERIALS AND METHODS: Pre- and postoperative data of 57 patients who received a cochlear implant (CIs) were retrospectively analyzed. For evaluation of subjective hearing ability the HISQUI questionnaire consisting of 19 questions was used as reference. Pure-tone audiometry and Freiburger monosyllable word tests were used as objective measurements for hearing. RESULTS: The mean HISQUI score increased on average from 53.0 prior to surgery to 69.0 after surgery. In addition, there were significant improvements in all seven subgroups of the questionnaire divisions. A correlation of rSp = 0.53 before surgery and rSp = 0.36 after surgery between the HISQUI scores and Freiburg monosyllable word test was recorded. In addition the 4FPTA (four frequency pure tone average) value correlated negatively with rSp = -0.48 with the HISQUI total score before surgery. CONCLUSION: The moderate correlation of both subjective and objective measurement methods underlines the importance of enquiring the patients' subjective perception and satisfaction. Through the combination of subjective statements and measurements of speech comprehension it is possible to obtain a comprehensive picture of the hearing performance of CI recipients.
EVALuna2:35452